Understanding the Challenges in Screening of Students with Specific Learning Disabilities: Insights from Educators, Parents and Psychologists - Batool, Aqsa; Sultan, Sarwat (Journal of Development and Social Sciences, 2024)
This study aimed to explore the challenges faced in screening and supporting students with Specific Learning Disabilities (SLDs) in Punjab, focusing on dyslexia, dysgraphia, and dyscalculia. The objective was to examine the barriers educators, psychologists and parents face in screening these disabilities and to identify the need for culturally relevant screening tools and teacher training. The study used a qualitative approach, conducting 3 focus group interviews with 10 educators, 10 special education professionals, and 10 parents using purposive sampling in the region. The findings revealed that teachers often struggled to differentiate between different types of SLDs due to a lack of standardized, culturally appropriate screening tools. Emotional and social difficulties, such as low self-esteem and social isolation, were also prevalent among students with SLDs. The study highlighted the urgent need for improved teacher education programs, locally developed screening tools, and more systemic support structures to address the needs of students with SLDs.